Synthesizing CuO/CeO2/ZnO Ternary Nano-Photocatalyst with Highly Effective Utilization of Photo-Excited Carriers under Sunlight - Kaiyi Luo (Nanomaterials, 2020)
The construction of heterostructured photocatalyst with an appropriate energy band structure will help realize highly efficient photo-excited charge separation. In this study, ternary CuO/CeO2/ZnO nano-particle (NP) composites were synthesized by a facile two-step sol-gel method, which exhibit significantly enhanced photocatalytic degradation performance for various organic pollutants under UV and visible light excitation. The photo-responses to both UV and visible light, as well as the visible light absorption and utilization rates of ZnO are found to be synergistically intensified by CeO2 and CuO co-coupling. The first-order kinetic constants (K) of 3%CuO/CeO2/ZnO for methylene blue (MB) degradation are ~3.9, ~4.1 and ~4.8 times higher than ZnO under UV light, visible light and simulated sunlight illumination, respectively. The roles of CuO and CeO2 in optical properties and photo-degradation under UV and visible light were explored. Besides, the photogenic holes (h+) of ZnO, CeO2, and the produced hydroxyl radicals (·OH) are proved to be the main active species under UV light. Dissimilarly, under visible light, the superoxide radicals (·O2−) formed by the reactions between oxygen molecules and the photo-generated electrons (e−) of CuO moving towards the catalysts surface are also found to be important for promoting dye decomposition. The improved photo-responses, the well-matched band structure that facilitates charge transfer processes, and the highly efficient utilization of the photo-excited carriers of the ternary nano-heterostructure are suggested to be the key factors for the remarkable enhancement of photocatalytic performance of ZnO nano-photocatalyst. This work offers a low-cost strategy to acquire highly active UV and visible light-driven photocatalyst.